Exploring the values and preferences of children and adolescents with obesity and their parents/caregivers concerning diet or physical activity interventions for weight management: Mega-ethnography of qualitative syntheses - Munira Essat; Christopher Carroll; Andrew Booth; Joanna Leaviss; Diana Castelblanco Cuevas; Roos Verstraeten (PLoS ONE, 2026)
Introduction Obesity and overweight are a global health problem affecting over 2.6 billion people worldwide. Diet and physical activity, including structured exercise, are critical components in the management of obesity. This review of reviews explores the values and preferences of children, adolescents, and their parents/caregivers that influence engagement and adherence to dietary and physical activity interventions for obesity management. Methods Eleven electronic databases were searched (from January 2010 to June 2024) to identify reviews incorporating qualitative research on values and preferences, attitudes or experiences of children or adolescents with obesity, or their caregivers, in relation to diet or physical activity interventions. Supplementary grey literature searching, citation searching and reference lists screening of included reviews were also undertaken. The methodological quality of included reviews was appraised using the Swedish Agency for Health Technology Assessment (SBU) tool. Data synthesis was performed using a mega-ethnography approach. Results Fourteen reviews were included with majority of studies conducted in high-income countries. Six key factors were identified that affect children and adolescents or their caregivers when initiating and continuing with physical activity and/or dietary management interventions. These included perceptions concerning the value of interventions; competing priorities; the role of social support; the physical environment; the nature and content of the intervention; and costs. Conclusion Multiple factors influence engagement with diet and physical activity programmes among children and adolescents with obesity and their caregivers, highlighting the need for emotional and psychological support, whole-family involvement, and personalised, trust-based guidance from health professionals. However, these findings are context-dependent with evidence primarily from high-income countries, which may limit their wider generalisability.